The Wiley handbook of eating disorders - Smolak, Linda, 1951-; Levine, Michael P. (Chichester, West Sussex ; Malden, MA : John Wiley & Sons, 2015)
"This groundbreaking two-volume handbook, edited by two of the leading authorities on body image and eating disorders research, provides evidence-based analysis of the causes, treatment, and prevention of eating disorders"--
Volume 1. Basic concepts and foundational research -- volume 2. Assessment, prevention, treatment, policy, and future directions.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Eating disorders -- Handbooks, manuals, etc; PSYCHOLOGY / Clinical Psychology; Eating disorders; Compulsive eating; Eating disorders -- Handbooks, manuals, etc; Food habits -- Psychological aspects; Handbooks and manuals; Electronic books; Electronic books